A Methodical Approach to Scrutinize the Role of Body Mass Index in Heart Rate Increment and Recovery - Zaman, Muhammad Haidar; Zhang, Yaoyuan; Ilyas, Muhammad; Yilin, Weng; Su, Yiwen; Bukhari, Ashfaq Ahmad Shah; Ahmad, Aousaf (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES Heart rate (HR) is a crucial health indicator and is also one of the health factors we need to pay explicit attention to. Body Mass Index (BMI) is considered a cofactor in heart-related issues like heart rate increment and recovery. Thus a study was conducted to determine the relationship between BMI and the rate of heart rate increment and recovery. METHODOLOGY 24 participants aged 17-20 were examined during elliptical machine training once a week continuously for three months. Their regular resting heart rate and change in heart rate during and after the elliptical workout were recorded and compared with BMI. RESULTS The HR increments were noted alongside BMI for male participants below BMI 21.13, and female participants below BMI 20.16. The heart rate increment tempo decreases alongside the increased BMI for both sexes afterwards. The heart rate recovery (HRrecovery) for male participants falls with the BMI increase to ~25 and increases thereafter. The female participants show a differing trend: HRrecovery rates increase following BMI growth till BMI ~ 20 and then decrease parabolically till the maximum BMI among female participants. The findings suggest no linear and non-significant correlation between BMI and heart rate increment or HRrecovery. The coefficient of determination is too tiny (R2 = 0.1395 for males and R2 = 0.003 for females) to indicate the causation between BMIs and HRrecovry. CONCLUSION This is the first study scrutinizing the role of body mass index on heart rate increment and heart rate recovery. Thus BMI should not be used as the cofactor or risk for heart activity or impaired functions.